Forest fire management expenditures in Canada: 1970-2013 [Dataset] - Stocks, B. J.; Martell, David L. (2016)
The csv formatted file named “Forest fire expenditures in Canada 1970-2013.csv” contains the Canadian forest fire expenditure data that is described in the paper entitled “Forest Fire Management Expenditures in Canada: 1970-2013” by B.J. Stocks and David L. Martell that was accepted for publication and will appear in Vol. 92, No. 3 (2016) of The Forestry Chronicle. The terms pre-suppression and suppression (or fixed and variable costs) are used to describe the two cost components of a fire management program. The pre-suppression costs include the fixed costs of hiring, training and equipping fire fighters, acquiring aircraft and constructing and maintaining buildings and other supporting infrastructure that are incurred or contracted for prior to the start of the fire season. Suppression costs include the extra costs incurred as the season progresses when fire fighters are called upon to work overtime, additional fire fighters are hired, extra aircraft are hired on short term leases and fire suppression resources are temporarily borrowed from other agencies. The codes used to designate each agency are, from west to east; British Columbia (BC), Alberta (AB), Saskatchewan (SK), Yukon Territory (YK), Northwest Territories (NT), Manitoba (MB), Ontario (ON), Quebec (QC), New Brunswick (NB), Nova Scotia (NS), Prince Edward Island (PE), Newfoundland and Labrador (NF), and Parks Canada (PC). All costs are expressed in thousands of Canadian dollars. Wildland Fire Management working group of the Canadian Council of Forest Ministers; Canadian Forest Service; Canadian Interagency Forest Fire Centre; Natural Sciences and Engineering Research Council of Canada